Cadmium Sulfide Quantum Dots Supported on Gallium and Indium Oxide for Visible‐Light‐Driven Hydrogen Evolution from Water. Issue 9 (18th July 2014) - Pan, Yun‐xiang; Zhuang, Huaqiang; Hong, Jindui; Fang, Zheng; Liu, Hai; Liu, Bin; Huang, Yizhong; Xu, Rong
Abstract In this work, CdS quantum dots (QDs) supported on Ga2O3 and In2O3 are applied for visible‐light‐driven H2 evolution from aqueous solutions that contain lactic acid. With Pt as the cocatalyst, the H2 evolution rates on CdS/Pt/Ga2O3 and CdS/Pt/In2O3 are as high as 995.8 and 1032.2 μmol h−1, respectively, under visible light (λ>420 nm) with apparent quantum efficiencies of 43.6 and 45.3 % obtained at 460 nm, respectively. These are much higher than those on Pt/CdS (108.09 μmol h−1), Pt/Ga2O3 (0.12 μmol h−1), and Pt/In2O3 (0.05 μmol h−1). The photocatalysts have been characterized thoroughly and their band structures and photocurrent responses have been measured. The band alignment between the CdS QDs and In2O3 can lead to interfacial charge separation, which cannot occur between the CdS QDs and Ga2O3. Among the various possible factors that contribute to the high H2 evolution rates on CdS/Pt/oxide, the surface properties of the metal oxides play important roles, which include (i) the anchoring of CdS QDs and Pt nanoparticles for favorable interactions and (ii) the efficient trapping of photogenerated electrons from the CdS QDs because of surface defects (such as oxygen defects) based on photoluminescence and photocurrent studies.